Studies on Transformations of Hemophilus influenzae : II. The molecular weight of transforming DNA by sedimentation and diffusion measurements - Goodgal, Sol H. (The Rockefeller University Press, 1961)
The sedimentation and diffusion coefficients have been determined for Hemophilus influenzae transforming activity and DNA using P(32)-labeled DNA. The methods employed the Spinco fixed boundary separation cell for measurements of the sedimentation coefficient and the Northrop-Anson diffusion cell to determine the diffusion coefficient. There was a very close correlation between the amount of DNA and transforming activity sedimented or diffused. The sedimentation coefficient (s (20°)), for both biological activity and DNA was 27 and the diffusion coefficient (D (20°)) 1 x 10(-8) cm(2)/sec. The molecular weight calculated from these coefficients gave a value of 16 million. There was no difference in the sedimentation coefficients for the two unlinked markers, streptomycin and erythromycin resistance, and the diffusion coefficients for single markers or the linked markers, streptomycin and cathomycin, were the same.